IMPACT OF INSTRUCTIONAL LEADERSHIP ON QUALITY ENVIRONMENT TOWARDS ENHANCING INSTITUTIONAL PERFORMANCE (Contemporary Journal of Social Science Review, 2025)
Instructional leadership is essential in the improvement of institutional performance and student achievement. Unlike traditional models of leadership, it focuses on core dimensions such as teaching, learning, and everyday school working. It promotes professional dialogue, appreciates teacher work, and demonstrates a growth mentality among students and teachers. The purpose of the study is to investigate the involvement of instructional leadership towards enhancing quality secondary school culture, to find out the relationship between institutional performance and quality environment of secondary school Faisalabad, to identify the challenges faced by instructional leadership in improving school performance, to examine the impact of instructional leader behaviour on institutional performance, and to provide baseline data for future leaders for enhancing institutional performance. A mixed methods approach will be utilized. Quantitative data will be collected using questionnaires and qualitative information will be collected using semi-structured interviews of secondary school heads and teachers. SPSS for quantitative analysis (descriptive statistics, Pearson correlation, ANOVA /t.test) and NVivo for qualitative themes will be employed for data analysis. The research is being conducted only in Faisalabad secondary schools and therefore may restrict generalizability of results. Determinants such as governance, school size, and culture may also influence the findings. The research does not consider broader issues such as education policy, government support, or social inequality but aims to contribute to evidence-based improvement strategies for schools.